Teachers’ Creativity in Improving Students’ Interest n Learning English - Hare Wisnu; Bangun Islam; M. Hidayatullah; Selamet Riadi Jaelani (LPPM Politeknik Pratama, 2023)
Language learning stands as a vital component of global education, fostering communication, cultural understanding, and personal growth. However, sustaining students' interest and motivation in learning a language can be a significant challenge for educators. This study explores the pivotal role of teachers' creativity in enhancing students' interest in language acquisition. Utilizing a qualitative descriptive research design with purposive sampling, the study gathers insights from language learners and teachers who have experienced the impact of creative teaching methods. Through in-depth interviews, classroom observations, and document analysis, the study examines how teachers' creativity influences students' engagement, intrinsic motivation, and language proficiency. The findings underscore the significance of engaging pedagogical strategies, such as gamification and storytelling, in capturing students' attention and enthusiasm. Moreover, the study highlights the importance of fostering a positive learning environment, where students feel empowered to express themselves and take ownership of their language learning journey.